Prevalence of bacteriologically confirmed pulmonary tuberculosis in South Africa, 2017–19: a multistage, cluster-based, cross-sectional survey. Issue 8 (August 2022) - Moyo, Sizulu; Ismail, Farzana; Van der Walt, Martie; Ismail, Nazir; Mkhondo, Nkateko; Dlamini, Sicelo; Mthiyane, Thuli; Chikovore, Jeremiah; Oladimeji, Olanrewaju; Mametja, David; Maribe, Phaleng; Seocharan, Ishen; et al.
Summary: Background: Tuberculosis remains an important clinical and public health issue in South Africa, which has one of the highest tuberculosis burdens in the world. We aimed to estimate the burden of bacteriologically confirmed pulmonary tuberculosis among people aged 15 years or older in South Africa. Methods: This multistage, cluster-based, cross-sectional survey included eligible residents (age ≥15 years, who had slept in a house for ≥10 nights in the preceding 2 weeks) in 110 clusters nationally (cluster size of 500 people; selected by probability proportional-to-population size sampling). Participants completed face-to-face symptom questionnaires (for cough, weight loss, fever, and night sweats) and manually read digital chest X-ray screening. Screening was recorded as positive if participants had at least one symptom or an abnormal chest X-ray suggestive of tuberculosis, or a combination thereof. Sputum samples from participants who were screen-positive were tested by the Xpert MTB/RIF Ultra assay (first sample) and Mycobacteria Growth Indicator Tube culture (second sample), with optional HIV testing. Participants with a positive Mycobacterium tuberculosis complex culture were considered positive for bacteriologically confirmed pulmonary tuberculosis; when culture was not positive, participants with a positive Xpert MTB/RIF Ultra result with an abnormal chest X-ray suggestive of active tuberculosis and without current or previous tuberculosis were considered positive for bacteriologically confirmed pulmonary tuberculosis. Findings: Between Aug 15, 2017, and July 28, 2019, 68 771 people were enumerated from 110 clusters, with 53 250 eligible to participate in the survey, of whom 35 191 (66·1%) participated. 9066 (25·8%) of 35 191 participants were screen-positive and 234 (0·7%) were identified as having bacteriologically confirmed pulmonary tuberculosis. Overall, the estimated prevalence of bacteriologically confirmed pulmonary tuberculosis was 852 cases (95% CI 679–1026) per 100 000 population; the prevalence was highest in people aged 35–44 years (1107 cases [95% CI 703–1511] per 100 000 population) and those aged 65 years or older (1104 cases [680–1528] per 100 000 population). The estimated prevalence was approximately 1·6 times higher in men than in women (1094 cases [95% CI 835–1352] per 100 000 population vs 675 cases [494–855] per 100 000 population). 135 (57·7%) of 234 participants with tuberculosis screened positive by chest X-ray only, 16 (6·8%) by symptoms only, and 82 (35·9%) by both. 55 (28·8%) of 191 participants with tuberculosis with known HIV status were HIV-positive. Interpretation: Pulmonary tuberculosis prevalence in this survey was high, especially in men. Despite the ongoing burden of HIV, many participants with tuberculosis in this survey did not have HIV. As more than half of the participants with tuberculosis had an abnormal chest X-ray without symptoms, prioritising chest X-ray screening could substantially increase case finding. Funding: Global Fund, Bill & Melinda Gates Foundation, USAID.